Влияние свойств микропорошков кубического нитрида бора на характеристики спеченных на их основе композитов и поликристаллов - Лошак, М.Г.; Александрова, Л.И.; Боримский, А.И.; Мельнийчук, Ю.А.; Белявина, Н.Н.; Заика, Н.И.; Лысаковский, В.С. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2009)
Properties of cBN micron powders prepared in various growth systems have been studied as
loose powders and in composites and polycrystals sintered of them at high pressure and temperature.
It has been found that mechanical properties of the composites and polycrystals, including
their cutting characteristics, depend not only on the initial powders properties, but also on the
method of producing the composites and polycrystals and conditions of testing them.